A "Common" Campaign: Reinventing the Book in Common Program on A Liberal Arts Campus. Issue 3 (2nd September 2019) - Strawser, Michael G.; Hume, Jessica
Abstract : If the book in common is truly an institutional endeavor, campus stakeholders (i.e., faculty, staff, and administrators) should feel some sense of ownership during the development phase of common book programs. Faculty, staff, and administrators play a crucial role in student development, and to ignore the voice of those campus stakeholders would do a disservice to common book programs and the overarching goal of student development. Thus, the purpose of this research, and the goal of this forum submission, is to explore faculty, staff, and administrator perceptions of the book in common on the campus of a small private liberal arts institution and to provide a voice for faculty, staff, and administrators regarding book in common proceedings moving forward.